2019
DOI: 10.1111/1744-7917.12715
|View full text |Cite
|
Sign up to set email alerts
|

Physical contact, volatiles, and acoustic signals contribute to monogamy in an invasive aggregating bark beetle

Abstract: The behavioral strategies and mechanisms by which some insects maintain monogamous mating systems are not well understood. We investigated the mating system of the bark beetle Dendroctonus valens, and identified several contributing mechanisms. Field and laboratory observations suggest the adults commonly form permanent bonds during host colonization. Moreover, it showed mated females that remained paired with males produced more offspring than mated females that were alone in galleries. In bioassays, a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…As D. valens is monogamous (Liu et al ., 2020), it is critical for a male to attain a female partner to have offspring and face intense competition since they attack in aggregations (Liu et al ., 2008). In our previous studies, we observed that the winning male enters the gallery made by the female and the loser male stays at the entrance of the gallery (Liu et al ., 2020). The male normally enters the female's gallery mostly within 1 h (Liu et al ., 2006).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As D. valens is monogamous (Liu et al ., 2020), it is critical for a male to attain a female partner to have offspring and face intense competition since they attack in aggregations (Liu et al ., 2008). In our previous studies, we observed that the winning male enters the gallery made by the female and the loser male stays at the entrance of the gallery (Liu et al ., 2020). The male normally enters the female's gallery mostly within 1 h (Liu et al ., 2006).…”
Section: Methodsmentioning
confidence: 99%
“…S1B and C), were simultaneously introduced into the pre‐drilled hole and resealed with iron mesh (20 replicates). As D. valens is monogamous (Liu et al ., 2020), it is critical for a male to attain a female partner to have offspring and face intense competition since they attack in aggregations (Liu et al ., 2008). In our previous studies, we observed that the winning male enters the gallery made by the female and the loser male stays at the entrance of the gallery (Liu et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the non-pioneering sex typically has welldeveloped stridulatory structures [11,12] and will stridulate (i.e., produce sounds/vibrations) when arriving near or inside the gallery of a pioneer's entry hole [13,14]. Airborne sounds and stridulatory structures of many bark beetles have been described [13,[15][16][17][18][19] and the ecological roles of stridulation in some bark beetle species are well studied [18,[20][21][22][23][24][25][26][27]. Interestingly, Insects 2021, 12, 496 2 of 19 bark beetle stridulation sounds influence pheromone production and composition of bark beetle partners within the tree.…”
Section: Introductionmentioning
confidence: 99%